The effectiveness of exercise-therapy on improvement of balance, gait, quality of life and depression in elderly patients with vertigo due to peripheral disturbances of vestibular system - Ehsan Ghasemi; Vahid Shayegannejad; Abbas Ghorbani; Negar Momeni; Fouzieh Khani (Vesnu Publications, 2010)
<!--[endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:"B Zar"; panose-1:0 0 4 0 0 0 0 0 0 0; mso-font-charset:178; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:8193 -2147483648 8 0 64 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:AR-SA;} p.abst, li.abst, div.abst {mso-style-name:abst; mso-style-unhide:no; mso-style-link:"abst Char"; margin-top:3.0pt; margin-right:0cm; margin-bottom:0cm; margin-left:0cm; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:11.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"B Zar";} span.abstChar {mso-style-name:"abst Char"; mso-style-unhide:no; mso-style-locked:yes; mso-style-link:abst; mso-ansi-font-size:11.0pt; mso-bidi-font-size:11.0pt; font-family:"B Zar"; mso-bidi-font-family:"B Zar";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} -->